(untitled) (Cadernos de Sociomuseologia, 2025)
The text presents the conception, curation, and assembly of the exhibition “About living, About resisting, About liberating,” conceived in 2024 by postgraduate students and professors from the Department of Museology at Lusófona University to discuss Hip Hop as a practice of memory, denunciation, and critical formation in the peripheries. The argument articulates the metaphor of Peripheral Islands to interpret the suburbs as unique and interdependent social ecosystems. The methodology, which is openly Afro-referenced, favours oral and audiovisual histories and artists’ statements, shifting the focus away from exclusively academic sources. The exhibition incorporated collective proposals from those involved with the aim of deconstructing the hegemonic narratives that sustained the idea of violence and associated it with poverty and skin colour to blame the favelas and ghettos, highlighting structural patterns of prejudice and inequality maintained by symbolic dispute. The results show public support (more visitors than formal guests), intergenerational recognition of repertoires, and debates on race, gender, and migration in the academic space. Keywords: (1) Hip Hop; (2) Sociomuseology; (3) Insurgency (4) Exhibition